CONSTRUCTION OF A TEACHING MODEL FOR CHINESE TRADITIONAL INSTRUMENTS FOR VISUALLY IMPAIRED STUDENTS IN SPECIAL EDUCATION SCHOOLS - Zhu, Jianyu; Rodsakan, Tepika; Soontorntanaphol, Nuttika (Fine Arts Journal: Srinakharinwirot University, 2026)
Background and Objectives: Vocational education serves as a crucial component of education for individuals with disabilities, holding profound significance for their independence and personal development. For these individuals, the ultimate purpose of education lies in enhancing life skills, social adaptability, and personal potential, thereby fostering self-actualization and societal contribution. Therefore, vigorously developing vocational education for people with disabilities is a vital measure to advance special education and improve its overall quality. This study aims to develop an instructional model for Chinese traditional instruments for visually impaired students, to help them enhance both their musical proficiency and self-identity. Methods: Through preliminary needs assessment and an investigation of the current situation, an instructional model for Chinese transitional instruments suitable for visually impaired students in special education vocational schools was constructed based on the survey results. Key Findings: This study establishes: a model comprising three core components: 1) the theoretical foundation and underlying logic of its construction; 2) the key supporting dimensions for its development; and 3) eight instructional principles for its implementation. Implications of the Study: This study three core implications: 1.Through implementation of this teaching model, more students with visual impairment can master Chinese traditional instruments, , secure suitable employment, improve their quality of life, enhance their self-identity, and better integrate into society. Through the framework provided by this study, special education vocational schools that previously lacked the teaching capacity or specialized faculty can smoothly establish and run Chinese traditional instruments ensemble courses. Through the design of this model, more people with visual impairment can deeply understand and master Chinese traditional instruments, thereby promoting and inheriting this Chinese traditional instruments among people with disabilities. Conclusions and Future Study: Theoretical Framework Adaptation: Centered on Outcome-Based Education (OBE) as the core framework, this approach integrates Kodály methodology (rhythmic recitation and solfege), flipped classroom practices (pre-class audio preparation in-class interactive activities), and traditional Chinese musical instrument pedagogy. It establishes a closed-loop logic of "needs – objectives – implementation – evaluation – optimization" to fully accommodate the sensory characteristics of visually impaired students, who rely primarily on auditory and tactile perception. Future studies should focus on empirically testing the longitudinal efficacy of this model across diverse special education settings. The core elements of the framework are clearly defined: The model incorporates seven influencing factors; activity design, teaching methods, learning methods, learning environment, artistic practice, professional guidance, and evaluation mechanisms, and focuses on four core competencies: single-instrument performance, technical mastery, independent practice, and stage art practice), By integrating these with external contextual factors such as student motivation and the campus environment, the model forms a comprehensive, multidimensional support system. Adaptation of teaching principles: This model establishes eight core teaching principles: (student-centered, multisensory integration, progressive learning, collaborative assistance, immediate feedback, safety and accessibility, cultural preservation, and sustainable development. These principles directly address the unique needs of visually impaired students, while simultaneously fostering skill cultivation, physical and mental development, and cultural heritage objectives. Future Research Perspectives on Model Practice Optimization: Long-term field experiments should be conducted across multi-regional special education schools to optimize the instructional systems by integrating longitudinal data on student skill development and employment outcomes Furthermore, personalized adaptation plans must be developed to cater to different types of visual impairments (such as total blindness and low vision) as well as specific musical instrument specialties. Resource and Faculty Development: Future efforts should focus on developing Braille audio versions of graded textbooks alongside intelligent auxiliary teaching aids; Additionally, a "theory + and practice" faculty training system should be established, paired with the construction of a national resource-sharing platform for instructional materials. Expansion of research scope: Future research should extend this model to compulsory education stages and other special groups such as students with hearing impairments. Additionally, it is essential to explore the model’s application within extracurricular clubs and artistic groups for individuals with disabilities. Technology and Policy Empowerment: This path involves introducing AI and VR technologies to develop immersive learning tools alongside advocating for policy support such as dedicated funding and curriculum design to enhance the "teaching employment" linkage mechanism. Cultural and International Reference: This dimension emphasizes integrating regional characteristics with Chinese traditional instruments and cultural connotations. Furthermore, it seeks to draw upon advanced international experiences to deepen the model’s localization and optimization.